Gothika - Silver, Joel.; Zemeckis, Robert, 1952-; Levin, Susan; Gutierrez, Sebastian; Kassovitz, Mathieu, 1967-; Berry, Halle; Downey, Robert, 1965-; Dutton, Charles S.; Lynch, John Carroll, 1963-; Hill, Bernard, 1944-; Cruz, Penelope; Harewood, Dorian; et al. (Burbank, CA : Warner Home Video, 2004)
Dr. Miranda Grey is a clinical psychologist who works alongside her husband, Doug, in the mental ward of a top security prison, where Miranda has been devoting much of her attention to a clever but deeply disturbed murderer named Chloe. One night, Miranda has a hideous nightmare in which a chance meeting with a strange young girl. Once she wakes, however, Miranda discovers that the real horror has just begun.
Originally released as a motion picture in 2003.
Special features: commentary by director Mathieu Kassovitz and director of photography Matthew Libatique; Limp Bizkit 'Behind blue eyes' music video; theatrical trailer.
Halle Berry, Robert Downey, Jr., Charles S. Dutton, John Carroll Lynch, Bernard Hill, Penelope Cruz, Dorian Harewood, Bronwen Mantel.
DVD, Region 1; 5.1 Dolby Digital.
Keywords: Clinical psychologists; Women prisoners; Violence in women; Feature films; Video recordings for the hearing impaired